António Victorino D'Almeida – Resonances in His Own Name. Considerations on Childhood, The Portuguese Music Scene and Artistic Education - Mateus Zagalo, Luís Manuel (2019)
The present article reflects about the long and rich creative life of António Victorino D'Almeida, one of the most brilliant artistic minds of our time, in the context of an interview and its interpretation. Composer, writer, producer, television and cinema director, stage director, pianist, conferencist, or even sketcher, his creativity is truly plural. His catalogue includes instrumental piano solo works, chamber music, symphonic pieces and choral-symphonic music, lieder, opera, cinematic, theatre scores, and fados, the Portuguese national song. He also approaches the theme of artistic education, both now and early in his career, as well as the challenges, expectations and setbacks of young musicians. This particular link has helped to build a substantial part of this article, according to the different roles that António Victorino D'Almeida plays in art, in his very own and refreshingly approachto cultural field, huge diversification and desmystifing speech. Building a striking originality either he uses musical notes, words or different kinds of forms. Above all, we had the chance to witness how his creative cosmos influences and interprets childhood, the Portuguese musical panorama and artistic education. Basically, the view of life itself.